THE CONTRIBUTION OF GIS IN INCREASING THE RESILIENCE OF BUMDES-BASED CREATIVE INDUSTRIES DURING THE COVID-19 PANDEMIC - Nindyo Cahyo Kresnanto; Rini Raharti; Retno Lantarsih; Raihan Iqbal Ramadhan; Dinda Novita (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Village Owned Enterprises (BUMDES) is legal entities formed by and for villages to manage enterprises and engage in various types of business for the best possible welfare of the village community. According to evaluations, most BUMDES were assumed to has declined in profit due to COVID-19 pandemic, and more than 45% of BUMDes having difficulties to survive. The purpose of this research is to investigate the state of BUMDES during and before the pandemic, this includes the issue of vulnerabilities for support recovery, as well as strategies on recovery both for the short and medium term.The research constructed on a literature review followed by initial investigation. The results of the questionnaire-based survey reflected the state of BUMDES and were presented in spatial distribution. The data analysis revealed that the COVID-19 outbreak had no major impact on BUMDES overall performance. Furthermore, finding based on BUMDES interview data, more than 75% respondent indicating that the pandemic had no influence on BUMDES performance. The findings also demonstrate that BUMDES could be labelld as small firm with great resilience (tangguh) in the presence of external conditions.